Relationships of circulating CD4+ T cell subsets and cytokines with the risk of relapse in patients with Crohn’s disease - Duclaux-Loras, Rémi; Boschetti, Gilles; Flourie, Bernard; Roblin, Xavier; Leluduec, Jean-Benoit; Paul, Stéphane; Almeras, Thibaut; Ruel, Karine; Buisson, Anthony; Bienvenu, Jacques; Josson, Cendrine; Jasnowski, Renaud; et al. (Frontiers in Immunology, 2022)
Background and Aims: We aimed to analyze circulating CD4+ T cell subsets and cytokines during the course of Crohn’s disease (CD). Methods and Results: CD4+ T cell subsets, ultrasensitive (us) CRP and various serum cytokineswere prospectively monitored every 3 months during one year, using multicolor flow cytometry and an ultrasensitive Erenna method in CD patients in remission at inclusion. Relapse occurred in 35 out of the 113 consecutive patients (31%). In patients in remission, within 4 months prior to relapse and at the time of relapse there was no significant difference in Th1, Th17, Treg and double positive CD4+ T cell subsets co-expressing IFN-Foxp3, IL-17-Foxp3 or IFN-IL-17. Compared to remission patients, the mean frequency and number of double positive IL-17 producing Foxp3+ CD4+ T cells and level of usCRP were significantly higher (p≤0.01) one to 4 months prior to relapse. At the time of relapse, significantly higher mean levels of IL-6 and usCRP were found (p≤0.001) compared to patients in remission. On multivariate analysis, high number of double positive IL-17-Foxp3 CD4+ T cells (≥1.4 cells/mm3) and elevated serum usCRP (≥3.44 mg/L) were two independent factors significantly associated with the risk of relapse. Conclusions: Detection of circulating double positive CD4+ T cell subsets supports the recent concept of T cell plasticity.